2008
DOI: 10.1088/0022-3727/41/12/125207
|View full text |Cite
|
Sign up to set email alerts
|

Modes of longitudinal combined discharge in low pressure nitrogen

Abstract: This paper reports the modes of a low pressure discharge in the combined (rf + dc) electric field. We propose to distinguish three modes of a longitudinal combined discharge (rf and dc voltages were applied to the same electrodes): (1) a non-self-sustained rf discharge perturbed by a dc electric field, (2) a combined discharge and (3) a non-self-sustained dc discharge perturbed by an rf electric field. The existence conditions of these modes are determined. The parameter range in which the first mode of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Simulation predictions regarding the behaviour of the dc and RF sheaths, the electron energy, and the plasma density with varying dc voltage are in qualitative agreement with experimental measurements (in nitrogen discharges) [82]. In particular, in figure 2 of [82] it is shown that, for dc voltages smaller than the RF voltage amplitude, the dc sheath width increases with the dc voltage, while the RF sheath width does not change. Moreover, figure 10 of [82] shows the plasma density decreasing and the bulk electron temperature increasing with the application of a small dc bias to a pure RF discharge.…”
Section: + Rf Capacitive Dischargesupporting
confidence: 81%
See 2 more Smart Citations
“…Simulation predictions regarding the behaviour of the dc and RF sheaths, the electron energy, and the plasma density with varying dc voltage are in qualitative agreement with experimental measurements (in nitrogen discharges) [82]. In particular, in figure 2 of [82] it is shown that, for dc voltages smaller than the RF voltage amplitude, the dc sheath width increases with the dc voltage, while the RF sheath width does not change. Moreover, figure 10 of [82] shows the plasma density decreasing and the bulk electron temperature increasing with the application of a small dc bias to a pure RF discharge.…”
Section: + Rf Capacitive Dischargesupporting
confidence: 81%
“…This is in part because, at high dc voltages, there is more significant acceleration of secondary electrons in the sheath of the dc electrode, as the inelastic collision mean free path is a decreasing function of energy, for electron energies above ∼70 eV [96]. Simulation predictions regarding the behaviour of the dc and RF sheaths, the electron energy, and the plasma density with varying dc voltage are in qualitative agreement with experimental measurements (in nitrogen discharges) [82]. In particular, in figure 2 of [82] it is shown that, for dc voltages smaller than the RF voltage amplitude, the dc sheath width increases with the dc voltage, while the RF sheath width does not change.…”
Section: + Rf Capacitive Dischargementioning
confidence: 54%
See 1 more Smart Citation
“…The temperature is determined from the slope of the linear region of lnðI electron Þ vs V Bias plot near the floating potential, 29,30 where I electron represents the electronic part of the probe current and V Bias represents the probe bias voltage. The plasma density is determined from the ion current using the results of the modified TALBOT and CHOU model.…”
Section: Experimental Set Upmentioning
confidence: 99%
“…We demonstrate that if we apply for combined discharge ignition an rf voltage exceeding the minimum voltage for igniting a selfsustained rf discharge, then the dependence of dc breakdown voltage against gas pressure in a chamber consists of two sections. Similar to [26] we propose to distinguish three modes of combined discharge ignition depending on the relation between dc and rf voltages applied across the discharge gap: (1) ignition of an rf discharge perturbed by a dc electric field; (2) ignition in combined fields; (3) ignition of a dc discharge perturbed by an rf electric field. On the ground of the analytical model we got the gas breakdown criterion in combined fields being valid for arbitrary rf and dc voltage values and for predicting the registered data satisfactorily.…”
Section: Introductionmentioning
confidence: 99%